Pengaruh Rasio Kinerja Bank Terhadap Profitabilitas Industri Bank Umum Syariah di Indonesia - Felix Efendy; Salman Fathoni (Jurnal Ilmiah Ekonomi Islam, 2019)
The purpose of this study was to determine and analyze the effect of the level of bank health ratios measured by BOPO, FDR and NPF on increasing the profitability of the Sharia Commercial Bank industry in Indonesia, which is proxied by ROA. The data used in this study are secondary data including operational efficiency (BOPO), liquidity (FDR), Non Performing Finance (NPF) and Return On Assets (ROA) in the sharia commercial bank industry registered at Bank Indonesia. The data is a monthly time series data from 2015-2018 obtained through the official sharia banking statistics website, Financial Services Authority (https://www.ojk.go.id). To analyze it, researchers used a multiple linear regression model with statistical tool software EViews 9. From the observations and analysis of the data that has been done, the conclusions in this study are the BOPO, FDR and NPF on ROA which is an indicator of the Bank's health to measure profitability has a high relationship . The BOPO variable partially has a significant negative effect on profitability (ROA). FDR partially has a negative and significant effect on ROA. NPF partially has no positive effect on profitability.